An Initial Study of the Emotional and Behavioral Characteristics of Black Students School Identified as Emotionally Disturbed. (February 2022) - Lambert, Matthew C.; Katsiyannis, Antonis; Epstein, Michael H.; Cullinan, Douglas
For years, the research and policy focus on Black students with emotional disturbance (ED) has been on racial disproportionality. The disproportionality issue has sparked professional debate and raised major questions about racial bias, cultural fairness, appropriateness of assessment instruments, the adequacy of special education programs, poverty, exposure to risk factors, and research approaches. Unfortunately, minimal progress has been made on understanding the overrepresentation of Black students in ED programs. The purpose of the present study was to initiate research on the emotional and behavioral functioning of Black students with ED, by comparing the teacher-completed ratings from the Scales for Assessing Emotional Disturbance for Black students with ED ( n = 139), Black students without ED ( n = 421), White students with ED ( n = 271), and White students without ED ( n = 1, 218). The results demonstrated that (a) Black students with ED were judged to demonstrate significantly higher levels of emotional and behavioral problems than their Black and White peers without ED, and (b) Black students with ED differed minimally from White students with ED. Research limitations, directions for future research, and implications for assessment and service delivery are discussed.